Physiological and Expressional Regulation on Photosynthesis, Starch and Sucrose Metabolism Response to Waterlogging Stress in Peanut - Zeng, Ruier; Chen, Tingting; Wang, Xinyue; Cao, Jing; Li, Xi; Xu, Xueyu; Chen, Lei; Xia, Qing; Dong, Yonglong; Huang, Luping; Wang, Leidi; Zhang, Jialei; et al. (Frontiers in Plant Science, 2021)
Waterlogging has negative effects on crop yield. Physiological and transcriptome data of two peanut cultivars [Zhongkaihua 1 (ZKH 1) and Huayu 39 (HY 39)] were studied under normal water supply and waterlogging stress for 5 or 10 days at the flowering stage. Results showed that the main stem height, the number of lateral branches, lateral branch length and stem diameter increased under waterlogging stress, followed by an increase in dry matter accumulation, which was correlated with the increase in the soil and plant analysis development (SPAD) and net photosynthetic rate (Pn) and the upregulation of genes related to porphyrin and chlorophyll metabolism and photosynthesis. However, the imbalance of source-sink relationship under waterlogging was the main cause of yield loss, and waterlogging caused an increase in the sucrose and soluble sugar content and a decrease in starch content, and decreased the activity of sucrose synthetase (SS) and sucrose phosphate synthetase (SPS), which may be due to the changes in the expression of genes related to starch and sucrose metabolism. However, the imbalance of source-sink relationship led to the accumulation of photosynthate in stems and leaves, which resulted in the decrease of the ratio of pod dry weight to total dry weight (PDW/TDW) and yield. Compared with ZKH 1, the pod dry weight (PDW) of HY 39 decreased more probably because more photosynthate accumulated in the stem and leaves of HY39 and could not be effectively transported to the pod.